2014
DOI: 10.3390/s140712191
|View full text |Cite
|
Sign up to set email alerts
|

On Plant Detection of Intact Tomato Fruits Using Image Analysis and Machine Learning Methods

Abstract: Fully automated yield estimation of intact fruits prior to harvesting provides various benefits to farmers. Until now, several studies have been conducted to estimate fruit yield using image-processing technologies. However, most of these techniques require thresholds for features such as color, shape and size. In addition, their performance strongly depends on the thresholds used, although optimal thresholds tend to vary with images. Furthermore, most of these techniques have attempted to detect only mature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(138 citation statements)
references
References 31 publications
2
134
0
2
Order By: Relevance
“…In [4], a combination of SIFT and SURF descriptors are extracted densely over the image to detect pineapples using SVMs. Pixel-based segmentation is used in [9] to detect tomatoes using manually specified colour features with decision trees. Nearest neighbour matching is used in [3] over colour and texture features extracted at key-points for berry detection.…”
Section: Related Workmentioning
confidence: 99%
“…In [4], a combination of SIFT and SURF descriptors are extracted densely over the image to detect pineapples using SVMs. Pixel-based segmentation is used in [9] to detect tomatoes using manually specified colour features with decision trees. Nearest neighbour matching is used in [3] over colour and texture features extracted at key-points for berry detection.…”
Section: Related Workmentioning
confidence: 99%
“…Numerous research efforts have been reported in the literature on the development of a machine vision system for image acquisition, fruit detection, and fruit localization for robotic harvesting of fruits (Parish and Goksel, 1977;Harrell et al, 1985;Yang et al, 2007;Baeten et al, 2008;Scarfe et al, 2009;Yamamoto et al, 2014). However, proper synthesization of the literature to provide a clear guidance on the state-of-the-art and potential future direction has been lacking.…”
Section: Introductionmentioning
confidence: 96%
“…In order to solve the overlapping problem in plantlets recognition, Pastrana and Rath (2013) developed a novel pattern recognition approach using an active shape model (ASM). Yamamoto et al (2014) applied the X-means clustering algorithm on the basis of K-means clustering to determine the optimal number of clusters and to detect individual fruit in a multi-fruit blob. Due to their similarities, fruit detection tasks can be conducted with the similar method for face recognition and detection.…”
Section: Pattern Recognition Approachesmentioning
confidence: 99%